Antimicrobial 2‐hydroxyisocaproic acid and chlorhexidine resist inactivation by dentine. (22nd May 2015) - Sakko, M.; Tjäderhane, L.; Sorsa, T.; Hietala, P.; Rautemaa, R.
Abstract: Aim: To compare the antibacterial activity of 2‐hydroxyisocaproic acid (HICA) with currently used root canal medicaments and to examine their interactions with potential inhibitors in nutrient‐deficient and nutrient‐rich conditions. Methodology: First, the antibacterial activity of single concentrations of HICA, calcium hydroxide solution or slurry, chlorhexidine digluconate or acetate was tested against Enterococcus faecalis with and without potential inhibitors: dentine powder (DP), hydroxyapatite or bovine serum albumin, in a low concentration of peptone water. Relative viable counts were determined by culture at 1, 24 and 48 h. In the second set of experiments, the activity of three concentrations of HICA was evaluated against two isolates of E. faecalis with and without potential inhibitors in nutrient‐rich thioglycollate broth using a modification of a standard microdilution method. The minimum bactericidal concentration was determined by culture at 1, 24 and 48 h. Results: Concentrations of ≥33 mg mL −1 of HICA were found to be bactericidal against E. faecalis in both nutrient‐deficient and nutrient‐rich environments at 24‐ to 48‐h incubation, whereas the initial activity of Ca(OH)2 slurry was lost at 48‐h incubation. HICA tolerated well all tested potential inhibitors up to 19 mg mL −1 . DP concentrations higher than this inhibited its activity in a dose‐dependent manner in both environments. DP demonstrated moderate antibacterial activity, and it enhanced the otherwise limited activity of Ca(OH)2 slurry and solution. DP did not impact on the activity of chlorhexidine. Conclusions: These results support the long‐term antibacterial activity of HICA and indicate its tolerance to clinically relevant concentrations of dentine and other inhibitors commonly present in the root canal system. Therefore, HICA may have potential as an interappointment medication in the treatment of root canal infections.